The Parameter Experimental on the Dry Cell Type of Water Electrolysis for the HHO Gas Production - Tria Puspa Sari; Afira Ainur Rosidah; M. H. B. Satria; Siti Chalimah; Amajida Sadrina; Ramadan Bimo Anggoro (Nusantara Science and Technology Proceedings, 2023)
The global energy crisis, stemming from the heavy reliance on depleting fossil fuel reserves, has become a critical concern for countries worldwide, including Indonesia. In recent initiatives, hydrogen gas has emerged as a promising alternative energy carrier, generated through processes like electrolysis, which breaks down compounds containing hydrogen. This research focuses on the utilization of water electrolysis using SS 316 L, Copper, and Aluminium plates with NaHCO3, NaCl, KOH, and NaOH as catalysts. The primary objective of this study is to determine the type of plate that can produce hydrogen with lower resistivity. The average power consumption for each plate is as follows: SS 316 L at 129.88 Watts, Copper at 199.41 Watts, and Aluminium at 499.45 Watts. From the research findings, it can be concluded that the use of SS 316 L plates with NaOH as the catalyst is the most effective combination in this study, as it results in higher hydrogen production with lower power consumption or greater efficiency compared to the others. In the future, it is hoped that the research can be continued using solar panels as an alternative power source to replace the electricity supply from the national grid (PLN).